Semiotics in the Poem Derai-Derai Cemara by Chairil Anwar - Gregorius Jonathan; Dara Tarigas; Salma Fauziah; Septiana Sulastri; Muhammad Thamimi (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
Poem is a literary work rich in symbolic meanings and signs that represent the inner experiences of the poet. One poem that contains profound meaning is Derai-Derai Cemara by Chairil Anwar. This research aims to analyze the meanings of signs contained in the poem through a semiotic approach. The method used in this research is a qualitative descriptive method with text analysis techniques. The data collection tools in this research include the text of the poem Derai-Derai Cemara and an observation guide in the form of a checklist instrument to identify and record the lines of the poem that contain signs, symbols, signifiers, and signifieds. The process of data analysis is carried out systematically through stages of identifying sign elements, classifying based on the concept of signifier and signified, and interpreting the symbolic meaning of each identified sign. Research data consists of the lines of the poem that contain signs, symbols, and meanings representing the poet’s existential experience. The results of the analysis show that the poem Derai-Derai Cemara contains various signs that represent the poet’s awareness of the journey of life, solitude, and reflections on death and human limitations. The symbol of falling cypress leaves is interpreted as a symbol of time that continuously passes and life that moves toward mortality. Through a semiotic approach, this poem demonstrates how linguistic signs are used by the poet to convey philosophical meanings about human life. Therefore, semiotic analysis helps readers understand the deeper meaning of the poem and enriches the interpretation of literary works.